Emotion Coaching sebagai Penanganan Kasus Toxic Parents dalam Tinjauan Hadis: Studi Pendekatan Psiko-Historis-Kontekstual - Wijaya, Krisna Hadi (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2025)
Toxic parents are something that every parent wants to avoid, both consciously and unconsciously. However, in reality, many of them still fall into the problem of toxic parents. One of the parenting patterns offered by psychologists is the emotion coaching pattern. Gottman as the initial initiator of the concept of this parenting pattern mentioned three main aspects: the ability to recognize children's emotions; an attitude of acceptance of children's emotions; and training in child emotional mapping. These three are intended to create a good emotional relationship between parents and children, as well as foster children's mentality and a positive sense of belonging to their parents. This article examines this by contextualizing it with the hadiths of the Prophet SAW. The study is a qualitative research whose data is taken from literature studies. The study uses a thematic hadith study model with a psycho-historical-contextual approach. From the review of the hadith, it seems that Gottman's formulation is found to be relevant between the two. The Prophet SAW. apart from being a leader of the people, he also called for the nobility of children and their virtues while practicing them. As a prophet, he also did not ignore his attitudes that might be considered 'anomalous' by people. Starting from letting a small child be pampered by him, even in a prayer position; dowrying a baby, and even being willing to clean the pee of a baby on his lap, and so on.